Prospect of E-Commerce for Cut Flowers in Malaysia: Consumers' Perspectives - Abuoazra, Ebtesam Abd Elkarim Salman (2003)
E-commerce is not well established in Malaysia despite its overwhelming invasion in the marketing of products and services worldwide and the potential benefits it offers. The study examines the prospect of Internet marketing of flowers in Malaysia from the consumers' perspectives. The research objectives are: to determine the pattern of flowers consumption and marketing; to assess the socio-economic profile of the flower's consumer in Malaysia; to assess Malaysian consumers' perception and attitude towards e-commerce; and to identify the factors that determine the adoption of electronic market for flowers. An online survey was conducted through www.bluehyppo.com and www.jaring.my to solicit consumer profile as well as their behavioral dimensions with regards to flower consumption and marketing behavior. A total of 357 respondents participated in the survey. The findings show that currently, the usage of Internet as a medium of transaction is still minimal. Generally, Malaysian consumers exhibit positive perception toward e- marketing for flowers. The pertinent factors underlying the consumers' decision framework are: delivery quality, speed of information; secure payment, sensory perception, quality of access and privacy. However, the study indicates that the relationship between the decisions to adopt e-commerce is positively related to delivery quality and payment security, whereas the relationship is negative with regards to privacy. Moreover, the study also found that socio-economics factors such as gender, marital status and monthly income are significantly related to e-commerce adoption decision. On the basis of these findings, an integrated approach to research in Internet shopping is highly recommended.